Changing trends in the incidence, management and outcomes of coronary artery perforation over an 11-year period: single-centre experience. Issue 1 (28th April 2022) - Umar, Hamza; Sharma, Harish; Osheiba, Mohammed; Roy, Ashwin; Ludman, Peter F; Townend, Jonathan N; Nadir, M Adnan; Doshi, Sagar N; George, Sudhakar; Zaphiriou, Alex; Khan, Sohail Q
Abstract : Introduction: Coronary artery perforation (CP) is a rare but life-threatening complication of percutaneous coronary intervention (PCI). This study aimed to assess the incidence, management and outcomes of CP over time. Methods: A single-centre retrospective cohort study of all PCIs performed between January 2010 and December 2020. Patients with CP were divided into two cohorts (A+B), representing the two halves of the 11-year study. Results: The incidence of CP was 68 of 9701 (0.7%), with an increasing trend over the two 5.5-year periods studied (24 of 4661 (0.5%) vs 44 of 5040 (0.9%); p=0.035). Factors associated with CP included chronic total occlusions (CTOs) (16 of 68 (24%) vs 993 of 9633 (10%); p<0.001), type C lesions (44 of 68 (65%) vs 4280 of 9633 (44%); p<0.001), use of intravascular ultrasound (IVUS) (12 of 68 (18%) vs 541 of 9633 (6%); p<0.001), cutting balloon angioplasty (3 of 68 (4%) vs 98 of 9633 (1%); p<0.001) and hydrophilic wires (24 of 68 (35%) vs 1454 of 9633 (15%); p<0.001). Cohorts A and B were well matched with respect to age (69±11 vs 70±12 years; p=0.843), sex (males: 13 of 24 (54%) vs 31 of 44 (70%); p=0.179) and renal function (chronic kidney disease: 1 of 24 (4%) vs 4 of 44 (9%); p=0.457). In cohort A, CP was most frequently caused by post-dilatation with non-compliant balloons (10 of 24 (42%); p=0.009); whereas in cohort B, common causes included guidewire exits (23 of 44 (52%)), followed by stent implantation (10 of 44 (23%)). The most common treatment modality in cohorts A and B was balloon inflation, which accounted for 16 of 24 (67%) and 13 of 44 (30%), respectively. The use of covered stents (16%) and coronary coils (18%) during cohort B study period did not impact all-cause mortality, which occurred in 2 of 24 (8%) and 7 of 44 (16%) (p=0.378) in cohorts A and B, respectively. Conclusion: The incidence of CP is increasing as more complex PCI is performed. Factors associated with perforation include CTO or type C lesions and use of IVUS, cutting balloon angioplasty or hydrophilic wires.